An Examination of Mental Health Among Students at the University of Witwatersrand, South Africa - Mokgadi Dikotla; Constance Matshidiso Lelaka (Baileo: Jurnal Sosial Humaniora, 2026)
Mental health among university students is a significant and growing concern, as students are often exposed to academic pressure, financial strain, social adjustments, and personal challenges during their studies. These stressors increase students’ vulnerability to mental health conditions such as stress, anxiety, depression, and burnout, which may negatively affect academic performance, social functioning, and overall well-being. Although many universities provide mental health support services, these services are frequently underutilized due to factors such as stigma, limited mental health awareness, cultural and religious beliefs, fear of judgment, and concerns regarding confidentiality. This study employed a qualitative research approach guided by a phenomenological research design to gain in-depth insights into students lived experiences of mental health and mental healthcare utilization. Data were collected through face-to-face semi-structured interviews, with participants selected using purposive and snowball sampling techniques. The data were analysed thematically. The findings revealed five key themes: students’ understanding of mental health, perceived causes of mental health challenges, the impact of mental health on students’ academic and personal lives, doubts regarding access to mental healthcare services, and suggested strategies to improve mental health service utilization. The study concludes that promoting mental health literacy, reducing stigma, and ensuring accessible, compassionate, and student-centered support services are essential for improving mental health outcomes. Furthermore, strengthening institutional policies and support structures is critical in fostering an inclusive university environment that prioritizes student well-being and supports academic success.